RECURRENT ENDOMETRIOSIS. RISK FACTORS - Светлана Сергеевна Ламонова; Светлана Ивановна Елгина; Екатерина Александровна Большанина; Елизавета Евгеньевна Большанина; Мария Дмитриевна Сокирник; Елена Владимировна Рудаева; Кира Борисовна Мозес (Мать и дитя в Кузбассе, 2025)
Endometriosis is a chronic gynecological disease in which endometrial—like tissue develops outside the uterus, causing a variety of clinical manifestations, including chronic pain, infertility, and other complications. The main current treatment for endometriosis is surgery to remove the foci of endometriosis. However, scientific studies show that the risk of recurrence remains significant even after successful surgical intervention.